Creating Value Through Alliances: Can Strategic Management of Partnerships Build a World-Leading UK Regenerative Medicine Industry? - Quirk, Robin A (2015)
Regenerative medicine (‘regen med’) is a growing sector that holds the promise of transforming patient care. Unfortunately, the regen med industry within the UK risks losing ground on international competitors. In terms of basic research, outputs are second only to the US. Commercially however it is much less competitive with the US, falls also behind Germany in terms of size, and is facing threat from countries such as Japan and China. There are many contributing factors (e.g. limited venture capital and public funds, poor NHS technology adoption, fragmented EU regulations). That said, many key components, such as cutting-edge research, clinical expertise, and Centres of Excellence, are in place.